USAGE OF CANDLE NUT SHELL WITH POWDER SIZE OF D - Yovial Yovial; Wenny Marthiana; Duskiardi Duskiardi; Habibi Habibi (Jurnal Agroindustri, 2017)
Recently around 60% of the hazelnut shell has the potential to become wasted material. The purpose of this research is to exploit waste hazelnut shell by examining the mechanical properties of composite   from the powder of hazelnut shell. Epoxy resin acts as a matrix mixed with a hazelnut shell powder as a filler with a composition of 20%, 30% and 40% wt. Both materials are mixed using a mechanical mixer with varying speed and stirring times. The resulting composite material is then tested by tensile, impact and hardness testing. The Taguchi method is used to optimize forming process parameters of the epoxy-powder hazelnut shell composite. Research shows that the forming process parameters give different effects for each different mechanical property. Research found out maximum tensile strength of composite material at 30% wt of powder hazelnut shell. Overall, the result of taguchi optimization for the forming process parameters in this study was 43.68 N/mm2 for tensile strength, 0.074 106 J/mm2 for impact strength and 98.57 SHN for hardness.Keywords: .